The Longman anthology of British literature - Damrosch, David (Longman, 2010)
This volume presents extensive selections from a wide range of underrepresented female writers like Mary Wollstonecraft, Dorothy Wordsworth, and Mary Robinson. “Perspectives” sections shed light on the period as a whole